Mini cooling fridge using Peltier / Muhammad Adam Abdullah, Noor Hafiz Noordin and Mohd Ghazali Mohd Hamami - Abdullah, Muhammad Adam; Mohd Hamami, Mohd Ghazali (School of Mechanical Engineering, 2023)
The objective of this project is to enhance energy efficiency by replacing the compressor with a Peltier device. The utilization of a compressor in cooling systems results in higher power consumption, leading to increased electric costs. Additionally, compressors themselves are relatively expensive compared to Peltier devices. To address these challenges, this study proposes the implementation of a Peltier device as the cooling agent in refrigeration systems, specifically in fridges. In this design, the cold side of the Peltier device will be attached to an inner aluminium plate within the fridge, while the hot side will be connected to an aluminium plate, heat sink, and fans, which will serve as a radiator. Power will be supplied by a 12V AC adapter, and extruded polystyrene will act as a thermal insulator. By adopting this approach, the Peltier device can effectively function as a cooling agent, leading to reduced electricity bills and production costs associated with fridges